Pengaruh Manajemen Konflik, Lingkungan Kerja, Prestasi Kerja terhadap Produktivitas Kerja PT. Sentral Bra Makmur Bogor - Putri Nur Ananda; Laksono Edhi Lukito; Ahmad Ahmad (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of conflict management, work environment, and work performance on employee productivity at PT. Sentral Bra Makmur Bogor. This type of research uses a quantitative approach with primary data sources obtained through questionnaires, literature studies, and observations. The study population was all 133 employees of PT. Sentral Bra Makmur Bogor, with a sampling technique using purposive sampling. Data analysis was carried out through several stages, namely the classical assumption test, descriptive analysis, instrument testing, multiple linear regression, t-test, F-test, and coefficient of determination (R²) test. The results of the instrument test indicate that all questionnaire items are valid and reliable. The classical assumption test proves the absence of multicollinearity, autocorrelation, or heteroscedasticity, and the residuals are normally distributed. Multiple linear regression analysis reveals that conflict management has no significant effect on work productivity, while the work environment has a positive and significant effect on productivity. This indicates that a good work environment can improve employee performance and productivity. In addition, work performance also has a positive and significant effect on productivity, which confirms that the better an individual's performance, the higher the productivity achieved. The results of the F test show a calculated F value of 132.418 > 2.67 with a significance value of 0.000 < 0.05, so it can be concluded that conflict management, work environment, and work performance simultaneously have a significant effect on work productivity. The coefficient of determination test produces an R² value of 0.749 or 74.9%, which means that the three variables are able to explain the influence on work productivity by 74.9%, while the remaining 25.1% is influenced by other factors outside this study, such as leadership style, work stress, and work motivation. This finding emphasizes the importance of managing the work environment and achieving performance in increasing company productivity.